Farm management practices associated with influenza A virus contamination of people working in Midwestern United States swine farms - Gustavo Lopez-Moreno; Marie R. Culhane; Peter Davies; Cesar Corzo; Matthew W. Allerson; Montserrat Torremorell (Porcine Health Management, 2023)
Abstract Indirect transmission of influenza A virus (IAV) contributes to virus spread in pigs. To identify farm management activities with the ability to contaminate farmworkers’ hands and clothing that then could be a source of virus spread to other pigs, we conducted a within-farm, prospective IAV surveillance study. Hands and clothes from farmworkers performing the activities of piglet processing, vaccination, or weaning were sampled before and after the activities were performed. Samples were tested by IAV rRT-PCR and virus viability was assessed by cell culture. A multivariate generalized linear model was used to detect associations of the activities with IAV contamination. Of the samples collected for IAV rRT-PCR testing, there were 16% (12/76) collected immediately after processing, 96% (45/48) collected after vaccination, and 94% (29/31) collected after weaning that tested positive. Samples collected immediately after vaccination and weaning, i.e., activities that took place during the peri-weaning period when pigs were about 3 weeks of age, had almost 6 times higher risk of IAV detection and had more samples IAV positive (p-value < 0.0001) than samples collected after processing, i.e., an activity that took place in the first few days of life. Both, hands and clothes had similar contamination rates (46% and 55% respectively, p-value = 0.42) and viable virus was isolated from both. Our results indicate that activities that involve the handling of infected piglets close to weaning age represent a significant risk for IAV dissemination due to the high level of IAV contamination found in farmworkers’ hands and coveralls involved in the activities. Biosecurity protocols that include hand sanitation and changing clothing after performing activities with a high-risk of influenza contamination should be recommended to farmworkers to control and limit the mechanical spread of IAV between pigs.